(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article deals with the historical underpinnings of idioms. The aim of the article is basically to define the meanings, origins and functioning of some English common idioms. It investigates the areas of this concept, characterizes the meaning of an expression and the meaning of the term “etymology” and the root idioms. This is because the meaning of an idiom doesn’t rely on the literal definition of its words, but rather the figurative context of how the words are used. Idioms are also cultural and social phenomena that reflect social mental characteristic of behavior, they relate to the communicative human behavior which suggests standards, rules and conventions of communication of this or that lingua-cultural community.